Marketing Mix Strategies Adopted by Selected Indian Business Outsources - Sundaram, N.; Geetha, S. (Indian Journal of Marketing, 2008)
Outsourcing refers to a transfer of some business functions or components of business process to an outside contractor. It is also defined as the transfer or delegation to an external service provider, the operations and day-to-day management of a business process. It is the outcome of recent technological change and new competitive environment.Business Process Outsourcing is becoming the norm because companies see outsourcing as an edge technology. Many companies begin to look at outsourcing not just as a quick fix, but also as an integral part of their long-term business strategy.